Waqaf Sajadah Untuk Dijadikan Masjid (Studi Analisis Literatur Fikih Syafi’i) - Adib, Ahmad Hidhir; Vina, Vina Wardatus Sakinah (Al-Inṣāf, 2022)
Endowing something is a noble deed, so this deed is highly recommended to be done. But keep in mind that if you have endowed something, then the ownership of the item, automatically transferred. The ownership of the goods that he endowed, then the authority of ownership passed to Allah SWT. So that the waqif can no longer monopolize the benefits of mauquf bih. This article will discuss the endowment of goods to be used as a mosque, in the sense that the goods will be a mosque. That is, if in general what is endowed to be a mosque is a piece of land, then this article will reveal the fact that it is possible to endow the pray rug. The urgency of knowing this qadiyyah is to get the reward of I’tikaf, which with us having a mosque in the form of a prayer rug, then the law of the mosque will apply to the prayer rug as if it could be made a place for I’tikaf. Of course this will make it easier for us to worship, because it can be entertained by doing other activities. But should also continue to come to the mosque, this concept is only a solution.